Stowaway: a new family of inverted repeat elements associated with the genes of both monocotyledonous and dicotyledonous plants. - Bureau, T E (1994)
Members of a new inverted repeat element family, named Stowaway, have been found in close association with more than 40 monocotyledonous and dicotyledonous plant genes listed in the GenBank and EMBL nucleic acid data bases. Stowaway elements are characterized by a conserved terminal inverted repeat, small size, target site specificity (TA), and potential form stable DNA secondary structures. Some elements are located at the extreme 3' ends of sequenced cDNAs and supply polyadenylation signals to their host genes. Other elements are in the 5' upstream regions of several genes and appear to contain previously identified cis-acting regulatory domains. Although the Stowaway elements share many structural features with the recently discovered Tourist elements, the two families share no significant sequence similarity. Together, the Stowaway and Tourist families serve to define an important new class of short inverted repeat elements found in possibly all flowering plant genomes.